Unveiling GPT-4o: Enhanced Multimodal Capabilities and Comparative Insights with ChatGPT-4 - Murad, Ibrahim A; Khaleel, Mustafa Ibrahim; Shakor, Mohammed Y. (International Journal of Electronics and Communications Systems, 2024)
Artificial Intelligence (AI), a rapidly advancing field in the modern era, particularly within computer science, continues to progress by developing tools with superior capabilities and innovative features. This study aims to conduct a comparative analysis between ChatGPT-4 and its enhanced version, ChatGPT-4o, based on various parameters. The methodology employs a mixed-methods approach using a standardized dataset and systematically designed prompts. The findings reveal significant improvements, including enhanced coherence and contextual relevance of generated content, accurate and verifiable citation presentation, and improved capabilities in addressing scientific, educational, and technical inquiries. Additionally, ChatGPT-4o demonstrates superiority in handling complex creative writing tasks, text analysis, and understanding intricate scientific, literary, and logical scenarios. These results collectively indicate that the outputs of ChatGPT-4o are more effective, making it a reliable tool for academic, professional, and technical purposes. This research highlights the significant impact of ChatGPT-4o on user interactions, showcasing its capacity to fundamentally transform content creation processes and analytical functions across various fields. The implications of this study suggest that ChatGPT-4o has the potential to enhance productivity and innovation in education, professional industries, and technological development